Ro-vibrational analysis of the hot bands of 13C2H4: ν7+ν10-ν10 and ν10+ν12-ν10; Journal of Molecular Spectroscopy; Vol. 317 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Kashirina N. V. Nadezhda Vladimirovna; Onopenko G. A. Galina Aleksandrovna; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann; Maul C. (2015, 2015)
Title screen